Severe Acute Malnutrition and Feeding Practice of Children Aged 6-59 Months in Pastoral Community, Afar, Ethiopia: Descriptive Cross-Sectional Study - Mulaw, Getahun Fentaw; Kase, Bizunesh Fantahun; Manchilo, Adebabay Dessie; Lombebo, Bereket Lopiso; Tollosa, Begna Melkamu (International Journal of Child Health and Nutrition, 2020)
Background: Severe acute malnutrition remains one of the most common causes of morbidity and mortality among children in developing countries, including Ethiopia. Knowing the local burden of SAM has huge importance for public health interventions. Therefore this study aimed to assess the level of severe acute malnutrition and feeding practice of children aged 6–59 months in Abaa’la district, Afar, Northeast, Ethiopia. Methods: Community-based descriptive cross-sectional study was conducted on 422 mother-child pairs of children aged 6–59 months. Kebeles were selected randomly after stratifying the district in to urban and rural, and study participants were selected using a cluster sampling technique. Data were collected using an interviewer-administered questionnaire, and child nutritional status was measured using WHO Mid upper arm circumference measuring tape. Data were entered into Epi data version 3.1 and exported to SPSS version 22 for analysis. The result was presented using Descriptive statistics. Results: The prevalence of severe acute malnutrition (SAM) was found to be 4.3% (95% CI, 2.3-6.1%) and that of moderate acute malnutrition (MAM) was 21.1 %. Almost all (98.8%) of children were ever breastfed. Prelacteal feeding and bottle feeding was practiced by 31% and 33.9% of children, respectively. Only 68.5% of children were feed colostrum. Around 45.5% of children were exclusively breastfed for the first six months, and 70.4% of children wean breastfeeding before the age of two years. Conclusion: The prevalence of severe acute malnutrition in the study area was lower than the regional figures, but still, it is a public health priority. There are improper child care and feeding practices. Therefore, public health interventions that can improve those practices should be strengthened.